La estrategia política de la izquierda comunista ante la cuestión religiosa en la Unión Soviética: una comparación con la actual izquierda española - Esquinas Algaba, José Ramón (Nómadas. Critical Journal of Social and Juridical Science, 2015)
The fall of the Soviet Union caused the transformation of a good part of the communist left in left indefinite once the institutional framework of rationality which guided the fifth generation disappeared. When we say that the Soviet State refrained from rationality to the communist left, we do so understanding the rationality as process given in the same transformations institutional recurrent and therefore, linked to materials defined contexts. We want to say in this, that the USSR forced the communist left to speak from the really existing socialism and to justify it - for better or for worse - from positive context. Could not speak for example, of a abstract pacifism and timeless when Soviet troops were fighting the Taliban in Afghanistan.
Keywords: Soviet Union; religion; Church-State separation